EXTRACTION, CLEAN-UP, AND HPLC DETECTION OF CARBARYL AND CARBOFURAN FROM CABBAGE (Brassica oleracea) - Iip Izul Falah (Indonesian Journal of Chemistry, 2009)
Carbaryl (1-naphthyl-N-methylcarbamate) and carbofuran (2,3-dihydro-2,2-dimethyl-7-benzofuranol-N-methylcarbamate) are very important N-methylcarbamate pesticides due to their high insecticide and nematocide effects, and widely used in vegetables plantations. The increasing use of carbamate pesticides poses a risk to human and environment. Thus, it is necessary to quantify their residue amount in food and vegetables to prevent harmful effect on animals, human and environment. This work was aimed to study of carbaryl and carbofuran analysis from fortified cabbage (Brassica oleracea) by liquid-liquid extraction, clean-up using SPE, followed by HPLC detection. Result of the work showed that detection of carbaryl using spectrophotometer detector at wavelength of 220 nm was better than at 230 and 280 nm, respectively. When the carbamates were extracted from cabbage using methanol, followed by liquid-liquid extraction using dichloromethane, cleaned-up with SPE-C18 and eluted by acetonitrile, the recovery was 96.8%. The detection by HPLC involved 4.6 x 25 mm, 5 µm C18 column, spectrophotometer detector at wavelength of 220 nm, and isocratic mobile phase at ratio of 35:65 of acetonitrile:aquabidest gave a good separation between co-extracted compounds and the carbamates.